Sex differences in lower extremity kinematics and patellofemoral kinetics during running - Almonroeder, T. G.; Benson, L. C. (Journal of Sports Sciences, 2017)
The incidence of patellofemoral pain (PFP) is 2 times greater in females compared with males of similar activity levels; however, the exact reason for this discrepancy remains unclear. Abnormal mechanics of the hip and knee in the sagittal, frontal, and transverse planes have been associated with an increased risk of PFP. The purpose of this study was to compare the mechanics of the lower extremity in males and females during running in order to better understand the reason(s) behind the sex discrepancy in PFP. Three-dimensional kinematic and kinetic data were collected as male and female participants completed overground running trials at a speed of 4.0 m · s-1 (±5%). Patellofemoral joint stress (PFJS) was estimated using a sagittal plane knee model. The kinematics of the hip and knee in the frontal and transverse planes were also analysed. Male participants demonstrated significantly greater sagittal plane peak PFJS in comparison with the female participants (P < .001, ES = 1.9). However, the female participants demonstrated 3.5° greater peak hip adduction and 3.4° greater peak hip internal rotation (IR). As a result, it appears that the sex discrepancy in PFP is more likely to be related to differences in the kinematics of the hip in the frontal and transverse planes than differences in sagittal plane PFJS.